The Impact of EU Law On the Definition of Advertising By Polish Courts Using Pharmacy Advertising as An Example - Weronika WOŹNA-BURDZIAK (Communications of International Proceedings, 2024)
Competition is one of the basic foundations of a free market economy, being at the same time the basis of freedom of economic activity. Competition has a positive impact not only on professional entities, motivating them to develop, but also on consumers, who, thanks to it, gain the possibility to choose. One of the pillars of competition is, of course, advertising. Advertising, which, as an economic phenomenon, is constantly evolving. This development has, of course, many positive aspects, but at the same time it obliges the authorities to take action to regulate it. The Polish legislator has rationed advertising in a number of specific acts, doing so mostly due to the need to protect superior values, such as human health or life. However, each aspect of advertising rationing first requires a definition of this concept, which under Polish law poses many problems of interpretation and practice. In this article, attention will be focused on the problem of advertising rationing on the part of the Polish legislator without simultaneous normative definition of this notion. The above imposes an obligation on the courts to define the notion of advertising in each case, which has led to the development of a certain scheme of definition, which includes, inter alia, reference to EU law. The main objective of this paper is to show the impact of EU law on the definition of the notion of advertising by Polish courts. The issue of legal definition of the notion in question is a complex problem, for the analysis of which the exemplification of pharmacy advertising was used. This example may be regarded as representative given the fundamental problems that will be addressed in the speech, while at the same time having special features of interest in the legal sense. In order to achieve this goal, a dogmatic-legal method has been used, which allows the examination of both the existing legal regulations and the jurisprudence and doctrine.
Keywords: Advertising; Pharmacies; Advertising Ban.